Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada SDN Jatisari II Kota Bekasi : The Influence of Leadership Style and Work Environment on Employee Performance at SDN Jatisari II Elementary School in Bekasi City - Dewi Vitaloka; Warsono Warsono (CV Warnak Johanna Nusantara, 2026)
Human resource management plays an important role in improving the quality of learning and employee work effectiveness. In achieving organizational goals, especially in educational institutions, employee performance is influenced by various factors, including leadership style and work environment. This study aims to determine the effect of leadership style and work environment on employee performance at SDN Jatisari II Bekasi City. This study uses a quantitative method with a statistical approach. Data collection was conducted through a Google Form-based questionnaire given to 37 teachers and staff respondents using a saturated sampling technique. Data analysis used data quality testing, classical assumption testing, multiple linear regression analysis, t-test and f-test, and coefficient of determination testing. The results showed that leadership style partially had a positive and significant effect on employee performance with a t-value of 5.649 > t-table 2.032 and significance of 0.000 < 0.05. The work environment also has a positive and significant effect on employee performance with a t-value of 2.074 > t-table 2.032 and a significance of 0.046 < 0.05. Simultaneously, leadership style has a significant effect on employee performance with a calculated f value of 110.215 > f table 3.28 and significance of 0.000 < 0.05